GURU DALAM KITAB MANHAJUS SAWI KARYA HABIB ZAIN BIN SMITH DAN RELEVANSINYA DENGAN KARAKTERISTIK GURU ABAD 21 (DUA PULUH SATU) - Rahman, Abdul; Suharto, Toto; Safira, Safira (Journal Education and Government Wiyata, 2024)
This research aims to find out educational material as an educator, and what are the guidelines for an educator from the perspective of Habib Zain bin Smith in the book Manhajus Sawi. As well as getting educational material that can be used in the 21st century. Then, relevant educational guidelines from Habib Zain bin Smith to the 21st century. This research uses library research methods with a qualitative method approach. The primary data source used in this research is the book Manhajus Sawi by Habib Zain bin Smith and the secondary data source is the Education Law in Indonesia, as well as supporting books, articles and scientific journals related to this research. The results of this research show (1) There are six materials for being an educator according to Habib Zain bin Smith, namely being objective, honest, ascetic, gentle, humble and respectful. (2) Educational materials according to Indonesian law, namely acting in accordance with Indonesian national religious, legal, social and cultural norms. Present yourself as a person who is honest, has noble character, and is a role model for students and society. Present yourself as a steady, stable, mature, wise person. Demonstrate work ethic, high responsibility, pride and confidence in being a teacher. Upholding the teacher's code of ethics. (3) Educational materials according to Habib Zain bin Smith's opinion and educational materials that have been stipulated by the Ministry of Education and Culture in the Republic of Indonesia Law have similarities, namely having the same goal of having good character and material. provided also explains how to have a good education in accordance with the 21st century. (4) Appropriate educational materials at this time can be applied to all elements of formal and non-formal educational institutions